Kajian Naratif dan Ironi Teologis: Teguran Allah melalui Keledai Bileam dalam Bilangan 22:21–35 - Tice Astria; Yesri Yohan Saputri; Januarti Januarti (Jurnal Budi Pekerti Agama Kristen dan Katolik, 2026)
This article examines Numbers 22:21–35 through narrative analysis and theological irony. The pericope of Balaam's talking donkey is one of the most unique narratives in the Hebrew Bible, combining supernatural elements with a profound theological critique of a mercenary prophet. This study aims to reveal how the author employs narrative irony as a vehicle for divine rebuke: God uses a mute animal to reprimand a prophet who should have been sensitive to His word. Using the narrative exegesis method that attends to plot, characterization, point of view, and dramatic tension, this article traces the theological meaning behind the irony. Findings indicate that this narrative is not merely miraculous but contains a critique of Balaam's ambiguous motivations between loyalty to God and temptation by material reward. The donkey, ordinarily silent, becomes an instrument of divine correction more obedient than the prophet himself. The theological implication is that God sovereignly uses any means to convey His will, including what is weak and despised by human standards.